Regulation of prostitution: guarantee of dignity or legal consecration of indignity - Tavares, Sandra (2018)
This article intends to address a contemporary topic in Portuguese political, social and legislative arenas: the adequacy of keeping the exploitation of prostitution as a crime or, otherwise, the pertinency of making it a legal activity, subject to regulation. The main methodology used will address the analysis of Portuguese internal laws (such as penal, labour and human rights laws) as well as international binding norms, in order to establish the ascertain legal option. In conclusion, the maintenance of the criminalization seems to be the coherent option.